Research on network capacity, absorptive capacity and service innovation performance of technology business incubators—based on PLS-SEM and fsQCA methods - Dong, Hao; Murong, Ruiyi; Li, Jian (Frontiers in Environmental Science, 2023)
Introduction: In the new economic normal, technology incubators are an important support to achieve the growth of strategic emerging enterprises. On the basis of resource based theory, organizational learning theory, inter-organizational relationship theory, and network capability theory, this study constructs a theoretical framework and hypotheses of the impact of network capability within the “resource-capability-relationship” perspective, absorptive capacity on service innovation performance of technology business incubators. Methods: This study uses 234 Chinese incubators in the incubator network as samples and applies partial least squares structural equation modeling (PLS-SEM) and fuzzy-set qualitative comparative analysis (fsQCA) to explore the questions mentioned above. Results: The results verify the relationship between network capacity, absorptive capacity, and service innovation performance. Furthermore, the results yield four paths that lead to high service innovation performance, such as “network capability orientation” and “high absorption orientation”, which are different combinations of network capacity and absorptive capacity. Discussion: The research results are important for improving the innovation performance of technology incubator services and ensuring the stable and effective operation of incubated enterprises.